If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6p+5=7p-48
We move all terms to the left:
6p+5-(7p-48)=0
We get rid of parentheses
6p-7p+48+5=0
We add all the numbers together, and all the variables
-1p+53=0
We move all terms containing p to the left, all other terms to the right
-p=-53
p=-53/-1
p=+53
| 24−r=58 | | 12x+2x-3=39 | | 3u^2+6u-9=0 | | 2(2q-7)=10 | | z=14+2/3 | | x-3/4x=28 | | x²+14x-15=0 | | y³=27 | | k²=225 | | 5x/2÷10=0 | | 8/2(1+3)=x | | 5x+2=7x4 | | 16x-1=5x+3 | | 4-3(z-2)=-34 | | -3/2z+23=1/24 | | 20x=(5-1) | | 3f=8.91 | | 4x+4=-2x+1 | | x^2-10/x-1=-14-x/x-1 | | Y=x^2-7x+1 | | 3x8=33x =3 | | 3x8=383x =3 | | 82=-2+7(2b-2) | | 4^2-4*2*k=0 | | 82=-2+7(2b-3 | | x+16/4=54 | | X+5=2x-17 | | 9/3y=63 | | 5/3x-8=13 | | 2/3x=x-6 | | 2/3x+1-4/x-3=0 | | 2b+4=3b+15 |